Analysis of Determinants of Sales Level of MSME Creative Food and Beverage Industries in Pancoran District, South Jakarta during the COVID-19 Pandemic - Rahayu Lestari; Mufidah Tamah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of Product Quality, Price Perception and Digital Marketing on the Sales Level of MSMEs in the Creative Food and Beverage Industry in Pancoran District, South Jakarta during the covid-19 pandemic. The data in this study used primary data through questionnaires to 100 respondents from SMEs in the Creative Food and Beverage Industry, Pancoran District, South Jakarta. This study uses a factor analysis method that is carried out on 30 variables that affect the Sales Level of SMEs in the Creative Food and Beverage Industry. Results of analysis Through factor analysis, it can be seen that the first factor that most dominantly affects the level of sales of food and beverage SMEs is the price that is able to compete with other products and innovation with other types of raw materials. So the hypothesis put forward that the price factor that is able to compete with other products as the dominant factor in influencing the level of sales of food and beverage SMEs is proven.